Application of QR codes as a new communication technology and interactive tourist guide in Jaboi, Sabang. Issue 1 (March 2020) - Marwan; Yanis, M; Muzakir; Nugraha, G S
Abstract: The Indonesian volcano is only limited for the electrical energy capacity, but in developed countries, the volcano is not only used for power plan but also developed for the tourism industry. Jaboi is one of the volcanoes located in Sabang with a capacity of 80 MW. The five potential of geothermal spots can be used as geo-tourism tours. Besides to improve the economic sector, the main purpose of the geo-tourism is the management of the tours that will be provided for educative lessons about the friendly life in a volcanic area. In this paper, we produced the educational videos that placed on each tourist spot; the video contains including the history of the site, geological background, and also information about the risks of living in a volcanic area. The QR code program is used as a medium for data transfer that can be scanned through a smartphone. This application is widely used in tourism as an economical alternative in technology. In the several spots that difficult to access, we also produced a safe route with a QR code program. The tracks will be overlaid on the smartphone with the 'gpx viewer' application, which possible to download from Google Play or App Store.